One hundred research questions in conservation physiology for generating actionable evidence to inform conservation policy and practice. Issue 1 (7th April 2021) - Cooke, Steven J; Bergman, Jordanna N; Madliger, Christine L; Cramp, Rebecca L; Beardall, John; Burness, Gary; Clark, Timothy D; Dantzer, Ben; de la Barrera, Erick; Fangue, Nann A; Franklin, Craig E; Fuller, Andrea; et al.
Abstract: Environmental change and biodiversity loss are but two of the complex challenges facing conservation practitioners and policy makers. Relevant and robust scientific knowledge is critical for providing decision-makers with the actionable evidence needed to inform conservation decisions. In the Anthropocene, science that leads to meaningful improvements in biodiversity conservation, restoration and management is desperately needed. Conservation Physiology has emerged as a discipline that is well-positioned to identify the mechanisms underpinning population declines, predict responses to environmental change and test different in situ and ex situ conservation interventions for diverse taxa and ecosystems. Here we present a consensus list of 10 priority research themes. Within each theme we identify specific research questions (100 in total), answers to which will address conservation problems and should improve the management of biological resources. The themes frame a set of research questions related to the following: (i) adaptation and phenotypic plasticity; (ii) human–induced environmental change; (iii) human–wildlife interactions; (iv) invasive species; (v) methods, biomarkers and monitoring; (vi) policy, engagement and communication; (vii) pollution; (viii) restoration actions; (ix) threatened species; and (x) urban systems. The themes and questions will hopefully guide and inspire researchers while also helping to demonstrate to practitioners and policy makers the many ways in which physiology can help to support their decisions. Abstract : Conservation physiology has emerged as an integrative action-oriented discipline. Yet, there remain many ways in which conservation physiology could further contribute to addressing the biodiversity crisis. We share a list of 100 research questions related to conservation physiology that, if answered, would enhance the conservation of biodiversity.